“Comparing the romantic attachments of young adults whose mothers were employed full time, part time or were stay-at-home mothers.” - Seth, Sumayya Cassim (My University, 2017)
Bowlby (1979, p. 129) posited that “attachment behaviour characterises the human being from the cradle to the grave.” These intimate attachments to other human beings are the hub around which a person’s life revolves, not only in childhood but throughout adolescence, the years of maturity and into old age (Bowlby, 1980). Much of Bowlby’s work focused on the early years of childhood and the attachment formed with caregivers at this time. With the development of the ‘Strange Situation’ procedure, researchers were able to empirically test Bowlby’s theory and have since been able to produce studies that looked at how the quality of attachment behaviours changed or remained stable over time (McConnell & Moss, 2011). A substantial amount of this research has been conducted on the effect of maternal employment and mother-child attachment. However, the research that has been conducted has only looked at the effect of maternal employment in the early years of the child’s life. No research could be found that measured the influence of early maternal employment status beyond second grade and into early adulthood. Furthermore, this research has not explored whether there are any reported differences between the employment status of mothers and the romantic attachments in young adults, internationally or in the South African context. A substantial focus has also been placed on exploring the possibility that the attachment styles identified in infancy continue into adulthood and play a role in romantic relationships, with Hazan & Shaver (1987) proposing romantic love as an attachment process. Research has shown that the quality of attachment relationships experienced in early childhood are related to the nature of later adult romantic relationships (Simpson, Collins, Tran, & Haydon, 2007). This study aimed to ascertain whether any associations existed between the romantic attachment styles of young adults, aged between 18-24 years old, and their mothers’ employment status during their childhood (i.e.: between ages 0 and 5). A sample of 446 participants completed an online questionnaire containing two sections: the first section ascertained demographic information while the second contained the Attachment Style Questionnaire (Feeney, Noller & Hanrahan, 1994). A series of Pearson chi-square were used to measure associations between a) the participants’ romantic attachment styles and their mothers’ early employment status, b) the participants’ age at which their mother returned to work and their romantic attachment style and c) maternal employment status and participants’ preference for their mothers to work or stay-at-home. Results for the overall romantic attachment style showed that regardless of early maternal employment status, the majority of the sample was avoidant in their romantic attachment style. Only 18.83% of the sample was securely attached and 1.79% was ambivalent in their romantic attachment. Results for the chi-squareds were all significant, indicating that an association does exist between the various constructs. Thematic content analysis (Braun & Clarke, 2006) was used to analyse data gathered on participants’ feelings toward their mothers’ employment status. Findings showed that participants with working mothers felt that their mothers were less available to them and provided less emotional and physical nurturance than they would have liked. Those with stay-at-home mothers indicated that they often experienced financial difficulty due to reliance on one income and that their mothers were sometimes perceived as too controlling; not allowing them enough space to explore the world for themselves.
A research project submitted in partial fulfilment of the requirements for the degree of Masters in Clinical Psychology Department of Psychology in the Faculty of Humanities University of the Witwatersrand, Johannesburg 2017
Keywords: Parent and child--South Africa; Attachment behavior--South Africa; Developmental psychology--South Africa